Pengaruh Pelatihan dan Karakteristik Wirausaha Terhadap Pengembangan UMKM (Studi Pada UMKM di Kecamatan Cigugur) - Alya Ilham Rizky; Rita Kusumadewi; Eef Saefulloh (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Micro, small and medium enterprises (MSMEs) have a contribution to make in supporting national economic development, including being able to absorb labor and produce goods and services at affordable prices for the needs of people with low incomes. Because of its role, the development of MSMEs needs to get great attention from the government and the general public. MSME actors need to continue to be trained and fostered in a sustainable manner so that they can be more developed and advanced. By participating in the training, MSME actors are expected to increase their knowledge and business capabilities, increase business management, generate new ideas, create business networks and increase business productivity. This study aims to determine the effect of training and entrepreneurial characteristics on the development of MSMEs in Cigugur sub-district. This study uses quantitative methods using data collection techniques through questionnaires. The population in this study MSME actors who are in Cigugur sub-district and have attended training with a sample of 70 people. The data analysis technique used is descriptive analysis and statistical analysis consisting of validity test, reliability test, classical assumption test, multiple linear regression test, hypothesis test in the form of t test (partial) and F test (simultaneous), and the coefficient of determination test (R2) with a test instrument the IBM SPSS version 22 application. The results of this study indicate that there is a positive and significant influence between training on MSME development, which is 10.28%, and there is a positive and significant influence between entrepreneurial characteristics on MSME development by 9.05%. Furthermore, simultaneously training and entrepreneurial characteristics have a positive and significant effect on the development of MSMEs by 19.3%.